Contribution The Contribution of Sharia Fintech to Increasing Financial Inclusion in the Muslim Community Amidst the Rise of Illegal Online Loans (Pinjol) in 2025: The Role of Sharia Fintech in Muslim Financial Inclusion in the Era of Illegal Loans - Echa, Esa Ayu Kusumaningtyas (Jurnal Ilmiah Ekonomi Islam, 2025)
The rise of illegal online lending (pinjol) practices in Indonesia in 2025 has created various economic and social problems, especially for Muslims who need fast financial access while remaining compliant with Sharia principles. This phenomenon has pushed the urgency of strengthening the role of Sharia fintech as an alternative financial service that is safe, transparent, and based on Sharia values. This study aims to uncover the contribution of Sharia fintech to increasing financial inclusion among Muslims amidst the high number of cases involving data fraud, bribery (riba), and unethical collection practices carried out by illegal pinjol. The research method used a qualitative approach with literature review techniques from various recent OJK regulations for 2024–2025, Sharia financial industry reports, and relevant research findings related to the development of Sharia fintech and the dynamics of illegal pinjol. The study's findings indicate that Islamic fintech not only provides access to financing based on halal contracts such as murabahah, qardhul hasan, and musyarakah, but also provides Islamic financial literacy education, increases public trust through transparent cost mechanisms, and supports financial stability through a more supervised digital ecosystem. The study concludes that optimizing technological innovation, strengthening regulations, and collaborating with the Islamic fintech industry, the government, and conventional Islamic financial institutions are key factors in maximizing the contribution of Islamic fintech to increasing financial inclusion while reducing dependence on illegal lenders. These findings can inform policymaking to strengthen the digital Islamic financial system and encourage economic empowerment of the Muslim community in the digital era of 2025.